The Lengthening of Non-Stressed Short Vowels in the Lithuanian Dialect of Eastern Aukštaičiai Uteniškiai - Jasiūnaitė, Birutė; Stundžia, Bonifacas (Kalbotyra, 1990)
The sporadic lengthening of non-stressed short vowels is interpreted as a result of analogical levelling caused by lexically restricted phonetic changes in the case of pretonic vowels and by morphological causes in the case of the posttonic ones. This phenomenon, as a rule, is not characteristic of native speakers of the older generation, and may be considered to be a signal of the break-up of the three-length vocalic system.